Silver Carp Bone Powder as Natural Calcium for Fish Sausage. Issue 3 (16th March 2018) - Hemung, Bung-Orn; Yongsawatdigul, Jirawat; Chin, Koo Bok; Limphirat, Wanwisa; Siritapetawee, Jaruwan
ABSTRACT: Although silver carp bones (SCB) are generated as waste, they are a natural source of calcium and have the potential to be a food ingredient. When the SCB had been soaked in hot sodium hydroxide (0.8%), autoclaved, and ground into SCB powder (SCBP), the total calcium content, analyzed by inductive coupled plasma-optical emission spectroscopy, was about 32%. X-ray absorption near-edge structure (XANES) spectroscopy specified hydroxyapatite as the major calcium component. The soluble calcium in SCBP was found to be 0.59% in de-ionized water. SCBP induced the cross-linking of proteins in minced fish after incubation at 40°C, as indicated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Fortification of SCBP at 0.0, 0.5, and 1.0% (w/w) in fish emulsion sausage resulted in a decrease of moisture content, while the fat and protein contents increased slightly. Total ash content in the sausage increased significantly, and total calcium content increased 15-fold in fortified SCBP. The hardness and gumminess values of sausage were improved with the addition of SCBP, while the microstructure was not altered by SCBP.